Preparing educators for global challenges: insights from pre-service teacher education - Anara Urkunova; Kerry J. Kennedy; Laura Karabassova; Dana Ryspayeva (Cogent Education)
In a rapidly globalizing world, fostering global competence (GC) is essential for equipping students with the knowledge and skills required to navigate interconnected societal and professional challenges. This study examined the self-awareness, attitudes and skills concerning GC among pre-service primary education teachers in Kazakhstan, emphasizing their understanding of GC and preparedness to instruct future students in this domain. Data were collected utilizing an explanatory sequential mixed-methods design, comprising surveys (n = 335) and semi-structured interviews (n = 20) conducted at five universities in Western Kazakhstan. The findings revealed that Kazakhstani pre-service teachers (PSTs) demonstrated a foundational awareness of global issues and a readiness to embrace GC, yet their comprehension frequently extended only to environmental issues and digital literacy. Participants expressed limited confidence in implementing GC in classrooms, underscoring the gap between theory and practice in teacher education programs. This study underscores the necessity for systemic reforms in Kazakhstan’s initial teacher education (ITE) programs to conform to international standards. By integrating theory with practice, such reforms can enhance educators’ confidence and competence, ultimately equipping students to thrive in a globalized world. These findings enhance the discourse on GC education, highlighting the challenges and opportunities in transitional contexts, such as Kazakhstan.